PREDIABETES - MODERN ENTITY WITH NUMEROUS RISK FACTORS - Marjanović Petković, Milica (Medicinski podmladak, 2023)
Prediabetes (PreDM), the seventh leading cause of mortality, is constantly on the rise. It is estimated that by 2035, the number of people affected by prediabetes will reach 471 million people of the total population. Whether a person with prediabetes will develop type 2 diabetes within the next year, or later, or maybe never, depends on numerous factors, some of which are modifiable (body mass index (BMI), waist circumference (WC), lipid status, smoking habits, physical activity). If a person measures postprandial blood glucose levels higher than 7,8 mmol/L, they have twice the cardiovascular risk compared to someone with normal glycemic control. Hyperinsulinemia causes insulin resistance and endothelial dysfunction, while hyperglycemia leads to oxidative radicals forming and activating proinflammatory cytokines. Prediabetes is often associated with obesity and lipid disorders, which further contribute to elevated cardiovascular (CV) risk in individuals with prediabetes. There is a significant number of undiagnosed individuals with prediabetes. Therefore, screening all individuals with risk factors, including proper screening measures such as coronary artery calcium (CAC) scoring, is crucial to assess and prevent cardiovascular risk. It is important to correct all risk factors, achieve normoglycemia in patients with mildly elevated blood glucose levels, initiate pharmacotherapy at the right time, and as a result, reduce the risk of cardiovascular diseases, cerebrovascular diseases, chronic kidney disease, cancer, and dementia.